Fetal programming and the consequences on progeny development - a review (Research, Society and Development, 2021)
The objective of this work was, through a literature review, to identify the main physiological and behavioral changes caused by fetal programming that affect the health and performance of the progeny in the postnatal life. Among the numerous factors that alter fetal formation, maternal nutrition during pregnancy has been strongly referenced in recent research. Maternal nutrition during pregnancy can alter fetal formation in numerous ways, so that the fetus adapts as quickly as possible to the uterine environment, and these changes are noticeable during the adult life of the progeny. In general, the literature suggests that maternal restriction during pregnancy can promote physiological and functional changes in fetal organs and tissues, preparing the organism to survive in challenging environments also in postnatal life. In addition, individuals who experienced restricted environments during fetal formation have a greater search for food and altered psychosocial behaviors, such as fear reactions, isolation and reactivity. Higher production efficiency and consequently lower age at slaughter of the progeny has been associated with better maternal nutrition during pregnancy, since these individuals have adequate fetal formation and, therefore, greater metabolic capacity of nutrients in intensive production systems that aim for maximum performance animal.